Katalog agama : koleksi Perpustakaan Nasional RI. - Perpustakaan Nasional (Indonesia); Yayasan KAWEDRI (Jakarta, Indonesia) (Jakarta : Kerjasama antara Perpustakaan Nasional RI dan Yayasan Kawedri, 1991)
Catalog of religions in the collection of the National Library of Indonesia.
Includes indexes.
Keywords: Perpustakaan Nasional (Indonesia) -- Catalogs; Religions -- Bibliography -- Catalogs